Randomised trial of cord clamping and initial stabilisation at very preterm birth - Duley, Lelia; Dorling, Jon; Pushpa-Rajah, Angela; Oddie, Sam J.; Yoxall, Charles W.; Schoonakker, Bernard; Bradshaw, Lucy; Mitchell, Eleanor J.; Fawke, Joe (BMJ, 2017)
Objectives: For very preterm births, to compare alternatives policies for umbilical cord clamping and immediate neonatal care.